Preoperative Thrombocytosis is Not Associated with Overall Survival in 309 Glioblastoma Patients - Marx, Sascha; Altmann, Robert; Baschin, Marcel; Paland, Heiko; Rauch, Bernhard; Kohlmann, Thomas; Schroeder, Henry W. S. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background In recent years, a correlation of thrombocytosis and a worse prognosis was shown for many solid cancers, including glioblastoma multiforme (GBM).Methods A retrospective review was performed for all patients with a histologically proven and first-diagnosed GBM between 2005 and 2015 in our department. Clinical and paraclinical parameters were acquired from patient documentation and structured for subsequent data analysis. The association of potential risk factors with overall survival was assessed using the Kaplan–Meier survival analysis and Cox regression.Results The present study includes 309 patients first diagnosed with primary GBM. Our analyses validate well-known risk factors of a decreased overall survival such as higher patient age, a larger preoperative tumor volume, Karnofsky performance status, extent of resection, tumor localization, and adjuvant treatment. However, no correlation was observed between a preoperative thrombocytosis, the mean platelet volume, leucocyte count, activated partial thromboplastin time (apTT), fibrinogen level, and acetylsalicylic acid 100 co-medication. Patients with preoperative hemoglobin below 7.5 mmol/L had decreased overall survival.Conclusion The present study, enrolling the largest numbers of patients assessing this topic to date, did not find any association between a preoperative thrombocytosis and overall survival in 309 patients with GBM.
Keywords: platelet count; overall survival; glioblastoma; aspirin; hemoglobin